Deciphering spaces of and for participation: The subversion of community participation and rights in the urban land restitution process of District Six - Fortuin, Alicia (School of Architecture, Planning and Geomatics, 2018)
The Land Restitution Act 22 of 1994 affords historically dispossessed person to return areas from which they were forcibly removed. With a focus on urban restitution this dissertation looks at why the restitution of land in District Six has been slow and fraught with frustrations and delays. This dissertation assess the participatory planning processes in the restitution and redevelopment of land in order to gain nuanced and deeper understanding of why, the state's ideal of restorative justice has not been realised. Through a qualitative research approach, the study focuses on the case of District Six, studying the spaces of participation from 1994 -2013. Findings reveal that many want a stake in District Six, none more so than the community themselves. The findings reveal how state-led spaces of participation remain tokenistic in nature and on the other hand community led spaces of participation offers historically marginalised groups an opportunity to realise their rights. Recommendations are aimed at how planners can intervene to improve these spaces and contribute to making more inclusionary spaces.